Covid-19 Vaccination Options for Immunosuppressed Cancer Patients - I Dewa Agung Panji Dwipayana (Universitas Airlangga, 2021)
Background: Currently, many COVID-19 vaccine candidates are being developed to end the pandemic; however, immunosuppressed cancer patients have been excluded from the participating criteria. It is important that they are able to examine their options for achieving immunity against COVID-19. Purpose: This review aims to discuss the available options that can be taken to vaccinate immunosuppressed cancer patients when no vaccine is being developed for their safety. Method: A literature study was conducted using Google Scholar, DOAJ, and GARUDA Library on November 2, 2020, focusing on articles examining vaccination guidelines for immunosuppressed cancer patients. Results: The search found 200 articles, which were curated to obtain 13 articles that satisfied all inclusion criteria. These consist of four guidelines, five reviews, and four research articles. Based on the literature, immunosuppressed cancer patients have the option to use the vaccines currently under development, with precautions set for live attenuated and potentially infectious vaccines. Vaccination timing also needs to be adjusted so as to fall at a certain time before or after the immunosuppressive condition. Moreover, a more complete COVID-19 immunity can be achieved through a synergy between individual vaccination and the construction of herd immunity. Conclusion: Most of the vaccines currently under development may be safe for cancer patients, being mindful of several considerations. Here, herd immunity can serve as a complement to individual immunity.